Early Effects of Abaloparatide on Bone Formation and Resorption Indices in Postmenopausal Women With Osteoporosis. (28th January 2021) - Dempster, David W; Zhou, Hua; Rao, Sudhaker D; Recknor, Chris; Miller, Paul D; Leder, Benjamin Z; Annett, Miriam; Ominsky, Michael S; Mitlak, Bruce H
Abstract: Anabolic osteoporosis drugs improve bone mineral density by increasing bone formation. The objective of this study was to evaluate the early effects of abaloparatide on indices of bone formation and to assess the effect of abaloparatide on modeling‐based formation (MBF), remodeling‐based formation (RBF), and overflow MBF (oMBF) in transiliac bone biopsies. In this open‐label, single‐arm study, 23 postmenopausal women with osteoporosis were treated with 80 μg abaloparatide daily. Subjects received double fluorochrome labels before treatment and before biopsy collection at 3 months. Change in dynamic histomorphometry indices in four bone envelopes were assessed. Median mineralizing surface per unit of bone surface (MS/BS) increased to 24.7%, 48.7%, 21.4%, and 16.3% of total surface after 3 months of abaloparatide treatment, representing 5.5‐, 5.2‐, 2.8‐, and 12.9‐fold changes, on cancellous, endocortical, intracortical, and periosteal surfaces ( p < .001 versus baseline for all). Mineral apposition rate (MAR) was significantly increased only on intracortical surfaces. Bone formation rate (BFR/BS) was significantly increased on all four bone envelopes. Significant increases versus baseline were observed in MBF on cancellous, endocortical, and periosteal surfaces, for oMBF on cancellous and endocortical surfaces, and for RBF on cancellous, endocortical, and intracortical surfaces. Overall, modeling‐based formation (MBF + oMBF) accounted for 37% and 23% of the increase in bone‐forming surface on the endocortical and cancellous surfaces, respectively. Changes from baseline in serum biomarkers of bone turnover at either month 1 or month 3 were generally good surrogates for changes in histomorphometric endpoints. In conclusion, treatment with abaloparatide for 3 months stimulated bone formation on cancellous, endocortical, intracortical, and periosteal envelopes in transiliac bone biopsies obtained from postmenopausal women with osteoporosis. These increases reflected stimulation of both remodeling‐ and modeling‐based bone formation, further elucidating the mechanisms by which abaloparatide improves bone mass and lowers fracture risk. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).